Tuberculosis vaccines: present and future. - Minassian, A; Mcshane, H (2008)
There has never been a greater need for a new protective tuberculosis vaccine. Bacille Calmette-Guerin remains the cornerstone of any vaccine strategy, but improving its immunogenicity and efficacy has now become an urgent global health priority. This review discusses the main vaccines currently in clinical development and other novel vaccine strategies in the pipeline. It addresses the key questions in vaccine design, including antigen selection, route of vaccine delivery and immune correlates of vaccine-induced protection. There is an opportunity to identify such correlates from ongoing and future Phase II/III trials and, as these emerge, they can be used to validate the most relevant and predictive animal models with which to develop the next generation of new vaccines.